PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. FUJI SEIMITSU INDONESIA - BEKASI - Riski Eko Ardianto; Ergo Nurpatria Kurniawan (Jurnal Pengembangan Wiraswasta, 2018)
Employee performance is something that is considered important for the company. Employees have high performance will certainly be able to work optimally so that the objectives of the institution itself will be easily achieved. Through the improvement of the working environment and working discipline expected the resulting performance can be optimized within the enterprise. In this study to determine the three variables that can affect employee performance (Y), the work environment variables (X1) and discipline (X2). Simultaneous and partially on the performance of employees at PT.Fuji Seimitsu Indonesia. Type of research is quantitative research. Methods of data collection using questionnaires with sempel amount of research is 100 respondents.Data analysis techniques in research using descriptive analysis, multiple linear regression analysis, validity and reliability test and partial test ( Test T) and a simultaneous test (Test F). Results of research conducted using SPSS 2.2 (ststitical program for social science), from the results obtained that the working environment (X1) were significant influence on employee performance (Y) on PT.Fuji Seimitsu Indonesia because work environment variables t = 3.231 > t table 1.660 with sig = 0.002 < 0.05. Labor discipline (X2) have a significant effect on employee performance (Y). Work environment (X1) and discipline (X2) simultaneously significant effect on employee performance (Y) PT. Fuji Seimitsu Indonesia.The results obtained on the whole of the working environment (X1) and discipline (X2) are all very significant influence on employee performance (Y) in PT.Fuji Seimitsu Indonesia.Â Keywords:Work Environment, Work Discipline and Employee Performance